Pemberdayaan Potensi Masyarakat dalam Melestarikan Budaya Daerah Jambi (Kesenian Kompangan) di Desa Mendalo Indah, Jambi - Kuswanto Kuswanto; Refnida Refnida; Irzal Anderson (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
The preservation of Kompangan art is generally carried out in the original area of Jambi. The rapid development of settlements, especially in the central area of offices, trade and education, needs to be balanced with the development of local culture so that there is no shift in cultural values. In response to this, the Jambi University LPM through the implementing team provided assistance to the community in empowering the potential to preserve the Kompangan arts and culture of the Jambi region. The service method used is socialization and collaboration. From this service activity, the community's potential in preserving Kompangan art was obtained, namely (1) there was 19.23 per cent of children and adolescents were interested and 50 per cent were very interested in learning and practicing kompangan art; (2) availability of adequate trainers; (3) there is potential for financing sourced from community infaq and shodaqoh; (4) receive support both morally and materially from the community. From these various potentials, a Kompangan arts institution was formed in Mendalo Indah village with the name "Compangan Al Banna Group" as a place for fostering and training kompangan arts for children and adolescents.